SISTEM INFORMASI MANAJEMEN DAN LAYANAN ASET TI MENGGUNAKAN FRAMEWORK CODEIGNITER - Benny Firmansyah (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
Management and maintenance of IT (Information Technology) assets is one of the main tasks of the Statistical Network and Reference Function at the office of BPS-Statistics of Sumatera Barat Province. This study aims to design and build management information systems and IT asset services starting from the allocation to the reporting process on the condition of IT assets. The method used in this research is prototyping with the evolutionary prototype type which consists of the user needs stage, creating a prototype, adjusting the prototype to the user's wishes, and using the prototype. The result of this research is a web-based IT asset management and service information system using the Codeiginiter framework. This system implements the QR Code labelling and the Telegram Bot notification feature in the IT asset service process. This system is able to answer the needs of organizations in producing up-to-date IT asset data reports and easy IT asset service processes.